Vocational Identity and Career Decision-Making Difficulties among Students in Bonded Scholarship Programs - Aurelia Hayfa Rayna; Talitha Lintang Pertiwi (Universitas Ahmad Dahlan, 2026)
This study examines the influence of vocational identity on career decision-making difficulties among bonded scholarship recipients in Indonesia. Bonded scholarship students face a unique psychological condition in which institutional career commitments are established prior to autonomous exploration, potentially placing them at risk of foreclosed vocational identity. Using a quantitative cross-sectional design, data were collected from 112 students selected through convenience sampling. Simple linear regression analysis revealed that vocational identity significantly and negatively predicted career decision-making difficulties (β = −0.519; p < 0.001), accounting for 26.9% of the variance. Additionally, male students demonstrated significantly higher vocational identity scores, while female students reported greater career decision-making difficulties. These findings highlight the critical role of vocational identity as a psychological factor in reducing career indecision, even within institutionally structured career pathways.